(untitled) (GYMNASIUM, 2009)
The accelerated pace of development of major world economies, the technological progress, the behavior and demands of a bigger and bigger mass of people, but also the worrying effects of global warming, generates international development trends in the area for winter sports and related industries, that need to be understood and undertaken by Romania in order to remain on the world map of engaging in such activities. The current level of global development of tourism, of industries and services in the area of winter recreational activities is very high. At this point, Romania should show more clairvoyance and realism in promoting the winter tourism policies.